2021
DOI: 10.3390/brainsci11070939
|View full text |Cite
|
Sign up to set email alerts
|

Early Visual Attention Abilities and Audiovisual Speech Processing in 5–7 Month-Old Down Syndrome and Typically Developing Infants

Abstract: Communicative abilities in infants with Down syndrome (DS) are delayed in comparison to typically developing (TD) infants, possibly affecting language development in DS. Little is known about what abilities might underlie poor communication and language skills in DS, such as visual attention and audiovisual speech processing. This study compares DS and TD infants between 5–7 months of age in a visual orientation task, and an audiovisual speech processing task, which assessed infants’ looking pattern to communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This study compared Down syndrome (DS) and TD infants between the ages of 5 and 7 months in a visual orientation test as well as an audiovisual speech processing task, which examined infants’ gazing patterns to communicative signals (i.e., face, eyes, mouth, and waving arm) by Pejovic et al in 2021 [ 62 ]. The study found that DS infants’ early visual attention and audiovisual speech processing may be disrupted, with implications for their communication development, suggesting new options for early intervention in this clinical population.…”
Section: Discussionmentioning
confidence: 99%
“…This study compared Down syndrome (DS) and TD infants between the ages of 5 and 7 months in a visual orientation test as well as an audiovisual speech processing task, which examined infants’ gazing patterns to communicative signals (i.e., face, eyes, mouth, and waving arm) by Pejovic et al in 2021 [ 62 ]. The study found that DS infants’ early visual attention and audiovisual speech processing may be disrupted, with implications for their communication development, suggesting new options for early intervention in this clinical population.…”
Section: Discussionmentioning
confidence: 99%
“…The initial automated speech analysis (ASA) and recognition techniques developed during the 1960s and 1970s could handle isolated sounds from a minimal to moderate vocabulary (Pejovic et al, 2021). Linear predictive coding was devised to accommodate voice tract differences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals with DS are superior in sustained attention to response task (SART) than auditory SART (Trezise et al, 2008). According to Pejovic et al (2021), children with DS are slower in orienting their visual attention to stimuli, and distinct relationships are shown between the visual attention difficulties and poor literacy, numeracy, and social skills (Erik et al, 2016). Therefore, it is suggested that the development of physical environment factors and presentation of educational materials in visual medium may facilitate improved attention of children with DS.…”
Section: Sustained Attention In Children With Ds: Visual Vs Auditorymentioning
confidence: 99%